Spatiotemporal variation of modern lake, stream, and soil water isotopes in Iceland - D. J. Harning; J. H. Raberg; J. M. McFarlin; Y. Axford; C. R. Florian; K. B. Ólafsdóttir; S. Kopf; J. Sepúlveda; G. H. Miller; Á. Geirsdóttir (Hydrology and Earth System Sciences, 2024)
As global warming progresses, changes in high-latitude precipitation are expected to impart long-lasting impacts on Earth systems, including glacier mass balance and ecosystem structures. Reconstructing past changes in high-latitude precipitation and hydroclimate from networks of continuous lake records offers one way to improve forecasts of precipitation and precipitation–evaporation balances, but these reconstructions are currently hindered by the incomplete understanding of controls on lake and soil water isotopes. Here, we study the distribution of modern water isotopes in Icelandic lakes, streams, and surface soils collected in 2002, 2003, 2004, 2014, 2019, and 2020 to understand the geographic, geomorphic, and environmental controls on their regional and interannual variability. We find that lake water isotopes in open-basin (through-flowing) lakes reflect local precipitation, with biases toward the cold season, particularly in lakes with sub-annual residence times. Closed-basin lakes have water isotope and deuterium excess values consistent with evaporative enrichment. Interannual and seasonal variabilities of lake water isotopes at repeatedly sampled sites are consistent with instrumental records of winter snowfall; summer relative humidity; and atmospheric circulation patterns, such as the North Atlantic Oscillation. Summer surface soil water isotopes span the entire range of seasonal precipitation values in Iceland and appear to be consistently overprinted by evaporative enrichment, which can occur throughout the year, although the sampling depths were shallower than rooting depths for many plant types. This dataset provides new insight into the functionality of water isotopes in Icelandic environments and offers renewed possibilities for optimized site selection and proxy interpretation in future paleohydrological studies on this North Atlantic outpost.